Between Tradition and Modernity: Customary Structures as Agents in Local Governance in Ghana. Issue 1 (April 2021) - Kwarkye, Thompson Gyedu
Local governance in many developing countries attracts several stakeholders who maintain a lot of significance in improving well-being, service delivery, accountability, and responsibility. The plural legal system where government structures exist side by side with customary structures in many countries south of the Sahara provides an opportunity to explore relationships, partnerships, and interactions among them. With ethnographic evidence from Kpandai District in Northern Ghana, this article explores customary structures not only as cultural and religious leaders with authority embedded in tradition but also as major stakeholders in local governance. The article argues that historical factors, coupled with limited government presence at the local levels, have positioned customary structures as an accessible channel to the people in the district. Customary structures have forged informal relationships and partnerships with government structures to bring the government closer to the people and to access basic services.